Climate Change Threatens Agriculture: Adapting for Food Security (CGIAR Climate Impact Platform Director, Aditi Mukherji, calls for climate and agri-food sector to work hand in hand in UNFCCC video) - UN Climate Change; CGIAR (2024)
The UN Climate Change Conference (COP 29) in Baku, Azerbaijan is all about implementing the Paris Agreement and ramping up ambition and action. Among the key priorities of COP 29 are securing a new goal on climate finance, ensuring every country has the means to take much stronger climate action, slashing greenhouse gas emissions and building resilient communities.